PENINGKATAN HASIL BELAJAR TENTANG BILANGAN BULAT MELALUI TAHAPAN-TAHAPAN PENYAJIAN J. BRUNER PADA SISWA KELAS IV SD KUTUKAN 5 RANDUBLATUNG BLORA (Improving Study Achievement on Integer through J. Bruner’s Presentation Steps to Students of Year IV, Kutuk (Jurnal Kreatif : Jurnal Kependidikan Dasar, 2010)
The background  of this research were dissatisfactory study achievement of the students of year IV, Kutukan 5 Primary School Randublatung Blora, and dissatisfactory capability of the teacher in teaching mathematic. The objective of this research was to improve students’ activity and study result, and also teacher’s capability in teaching integer by applying Bruner’s presentation steps. The results of this research showed that the use of Bruner’s presentation steps could improve students’ activity in learning integer. The data showed that students’ average score in activity improved, score 2.1 at cycle one, 2.3 at cycle two, and 2.4 at the last cycle. The second result was that the students’ achievement in mathematics improved. The data for this result was the students got average score 65 at cycle one, 69 at cycle two, and 80 at the last cycle. The last result of the research was that teacher’s capability in teaching integer also improved. In sequence he/she got score 1.4 at cycle one, 2.0 at cycle two, and 2.6 at cycle three. Keywords: students’ achievement in mathematics, integer, J. Bruner’s presentation steps